IMPACT OF EMOTIONAL INTELLIGENCE ON JOB AUTONOMY - A. Soomro, Fayaz; Khan, Dr. Sadaf; Khan, Jehanzeb; Mehmood, Wajid; Ullah Jan, Farman (The journal of contemporary issues in business and government, 2022)
Emotional Intelligence has great importance in human life as an individual whether in society or organizations. A number of schools of thought have well tried to dig out the impact of Emotional Intelligence on different aspects. Emotional Intelligence is a science that enables man how to cope with existing and anticipated issues at work place in general and Job Autonomy in particular. Some scholars opine that job autonomy is important factor that enables employees to have mastery over work environment. It gives impetus to get grip over organizational ecology. Employees having emotional mastery exceed within organizations as per contemporary and anticipated changes. The under reference paper has witnessed that there is greater impact of El over Job Autonomy. The data has been gathered from Middle and Top Management of public and private sector organizations. The survey contained a questionnaire and the data has been analyzed with the help of SPSS and other statistical procedures. However, it is found that there is impact of Job Autonomy at the workplace. Job Autonomy enables individuals to contribute at their whims and caprice without any formal or informal set-back.